Patenting Traditional Medicine - Eiland, Murray Lee (Munich Intellectual Property Law Center - MIPLC, 2009)
Traditional medicines have and will continue to form the basis of modern pharmaceuticals. Many indigenous communities are claiming rights in pharmaceuticals derived from their traditional medicine. In the past, such knowledge derived from non-western communities was largely regarded as free information. This has led some to attack the patent system as an ex-ploitative tool of the developed world. The first part of this analysis deals with the kind of protection provided in national legislation. Methods of protecting traditional medicine in India and China receive special attention. The second major issue covered in this volume is the kind of protection offered to TM of other countries in the west, including international agreements. America is a particular focus, as it is here that many of the battles over patenting traditional medicine are fought. While no uncon-troversial answers can be given in this debate, at least the relative strengths and weaknesses of various positions can be assessed. Dr. Murray Eiland received a doctorate in Oriental Archaeology from Oxford University and an LLM from the Munich Intellectual Property Law Center. He currently works at Charles Henry & Co., London as a (non-practising) Barrister.